Enablers and barriers affecting medication-taking behaviour in aging men with benign prostatic hyperplasia. (10th June 2013) - Kusljic, Snezana; Manias, Elizabeth; Tran, Ben; Williams, Allison
Abstract: Objectives : To identify the enablers and barriers affecting medication-taking behaviour in aging men with benign prostatic hyperplasia. Methods : A total of 40 patients attending the urology outpatient clinic in Melbourne in 2012 were screened. Patients who successfully met the inclusion criteria were interviewed using a structured interview schedule. Information regarding the patient's medication, demographic data and presence of co-morbidities was collected. Content analysis was compared with patient demographic and medical data, contributing to the analysis. Results : Problems with medication-taking were reported in 58% of patients. All patients without co-morbidities reported issues regarding their medications, whereas only 27% of patients with co-morbidities reported concerns regarding their medications. Statistical analysis revealed that patients without co-morbidities were significantly more likely ( p = 0.002) to have complaints with their medications compared to those with co-morbidities. Furthermore, patients with co-morbidities who required help of caregivers to assist with their medication-taking were significantly less likely ( p = 0.05) to have complaints with their medications compared to patients who self-managed. Conclusions : Older patients with caregivers who assisted managing their medication-taking had better adherence. Those receiving aid from their caregivers were significantly less likely to have complaints regarding their medications as opposed to those not requiring a caregiver. This highlights the importance of having support for medication-taking in patients with co-morbidities to assist with better adherence.